Pengurangan Emisi Gas Rumah Kaca dengan Penerapan E-Reporting System di Pertambangan PT Bukit Asam - Bima Arifiyanto; Rizky Mustika Sindu (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Arifiyanto B, Sindu RM. 2020. Reducing greenhouse gas emissions by implementing e-reporting system in PT Bukit Asam mining unit. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xxx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Coal mining activities are one of the activities that produce high greenhouse gas emissions. The purpose of this research is to calculate the success of reducing greenhouse gas emissions by implementing an E-Reporting System application in administrative reporting activities. This calculation uses a comparison basis before and after application of this technology with tier 2 emission factor approach according to the guidelines for the National Greenhouse Gas Inventory. E-Reporting System is one of the applications of the latest Industry 4.0 technology in the mining reporting system. This system succeeded in replacing previous system which was still conventional by eliminating use of operational vehicles for mining reporting. Through this program the company was able to save on fuel consumption and quantification of environmental improvements due to changes in this system succeeded in reducing greenhouse gas emissions by 3,355 tCO2e per year. Implementation of the E-Reporting System application can reduce GHG emissions generated in mining operations.